SIGNIFICANCE OF ANATOMICAL STRUCTURE AND PHYSIOLOGICAL FUNCTIONS IN LEARNING SWIMMING TECHNIQUES - D.T. Tursunova (American Journals Publishing, 2023)
In the process of learning swimming techniques, the importance of the athlete's anatomical structure and physiological functions has been explained.
Keywords: In the process of learning swimming techniques, the importance of the athlete's anatomical structure and physiological functions has been explained.